EGFR‐mutant lung adenocarcinoma associated with antisynthetase syndrome successfully treated with osimertinib. Issue 9 (7th March 2021) - Hara, Reina; Kanazu, Masaki; Iwai, Ami; Kuge, Tomoki; Ishijima, Mikako; Uenami, Takeshi; Akazawa, Yuki; Yano, Yukihiro; Yamaguchi, Toshihiko; Mori, Masahide
Abstract: Here, we report a rare case involving a 66‐year‐old man with epidermal growth factor receptor (EGFR)‐mutant lung adenocarcinoma and antisynthetase syndrome (ASS) treated with osimertinib. The patient presented with respiratory failure and bilateral pulmonary opacities; he was diagnosed with ASS accompanied by interstitial lung disease (ILD), consistent with paraneoplastic syndrome. After steroid pulse therapy, osimertinib was administered for lung adenocarcinoma without ILD exacerbation. Osimertinib could therefore be a treatment option for EGFR ‐mutant lung cancer with paraneoplastic ILD. Abstract : We report a case involving a patient with epidermal growth factor receptor‐mutant lung adenocarcinoma and antisynthetase syndrome accompanied by interstitial lung disease (ILD), treated with osimertinib. After steroid pulse therapy, osimertinib was administered for the lung adenocarcinoma, without ILD exacerbation. Osimertinib could be a treatment option for EGFR ‐mutant lung cancer with paraneoplastic ILD.